2016
DOI: 10.1111/nph.13947
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary loss of light‐harvesting proteins Lhcb6 and Lhcb3 in major land plant groups – break‐up of current dogma

Abstract: SummaryPhotosynthesis in plants and algae relies on the coordinated function of photosystems (PS) I and II. Their efficiency is augmented by finely-tuned light-harvesting proteins (Lhcs) connected to them. The most recent Lhcs (in evolutionary terms), Lhcb6 and Lhcb3, evolved during the transition of plants from water to land and have so far been considered to be an essential characteristic of land plants.We used single particle electron microscopy and sequence analysis to study architecture and composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 44 publications
3
45
0
Order By: Relevance
“…In that sense, a recent study of the photosynthetic apparatus in conifers revealed that the Pinaceae and Gnetales families lack the Lhcb3 and Lhcb6 proteins, which play a role in NPQ. Until now, this had been considered to be an essential characteristic of land plants (Kouril et al ). It is known that some antenna proteins play an important role in NPQ, as they interact with PsbS, facilitating the NPQ process (Kovács et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In that sense, a recent study of the photosynthetic apparatus in conifers revealed that the Pinaceae and Gnetales families lack the Lhcb3 and Lhcb6 proteins, which play a role in NPQ. Until now, this had been considered to be an essential characteristic of land plants (Kouril et al ). It is known that some antenna proteins play an important role in NPQ, as they interact with PsbS, facilitating the NPQ process (Kovács et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, antennae protein composition is of paramount importance in the response under stress. Very recently, Kouril et al () challenged a widely accepted concept. They discovered that some species from the Pinaceae family present lhcsr‐like transcripts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that none of the P. patens Lhcb4 (PpLhcb4; "Pp" for P. patens, hereafter) isoforms are related to AtLhcb4.3 [6], which is found only in dicots and is now classified as Lhcb8 due to its distinct function from AtLhcb4.1 and AtLhcb4.2 [22]. Further, as the ortholog of AtLhcb6 has not been found in green algae so far [11,12], the presence of an AtLhcb6 ortholog in P. patens suggests its uniqueness to land plants, although it is absent in Pinaceae and Gnetales, similar to the case of Lhcb3 [21]. In addition to major and minor LHCIIs, the ortholog of AtLhcb7, which is rarely expressed [22], is present in P. patens [6].…”
Section: Introductionmentioning
confidence: 95%
“…reinhardtii does not, suggesting its acquisition during plant terrestrialization [6] (however, Lhcb3 appears to have been lost during the divergence of Pinaceae and Gnetales [21]). The orthologs of three minor LHCII proteins (Lhcb4, Lhcb5, and Lhcb6) in A. thaliana are also found in P. patens [6].…”
Section: Introductionmentioning
confidence: 99%